Sur la convergence des series de Dirichlet - Miškelevičius, A. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Мишкелявичус. О сходимости рядов ДирихлеA. Miškelevičius. Dirichle eilučių konvergencijos klausimu